Role of siderophore in Pseudomonas fluorescens biofilm formation and spoilage potential function. (February 2023) - Chen, Jian; Sun, Zhihua; Jin, Jiamin; Wang, Feifei; Yang, Qing; Yu, Hejun; Yu, Jingyi; Wang, Yanbo
Abstract: We investigated the function of pyoverdine in the biofilm formation, motility, and spoilage potential of Pseudomonas fluorescens . We targeted and identified two major genes ( pvdA and pvdE ) that are involved in the biosynthesis of siderophores. We next constructed Δ pvdA and Δ pvdE mutants of P. fluorescens PF08 and found that the deletion of pyoverdine led to a biofilm-to-motivity transition as both Δ pvdA and Δ pvdE mutants displayed enhanced motility, reduced level of exopolysaccharides (EPSs), and attenuated biofilm formation. In addition, the lack of synthesis of pyoverdine promoted the spoilage of fish fillets stored at 4 °C. Based on the effect of pyoverdine deletion on the phenotype; we report that pyoverdine regulates the transcription levels of htpX, phoA, flip, flgA, and RpoS, suggesting that pyoverdine-mediated iron absorption may affect the regulation of flagellum and stress resistance. This study emphasizes the important role of pyoverdine in the formation of biofilm, motility, and spoilage of P. fluorescens PF08. Highlights: Two pyoverdine biosynthesis-related genes, pvdA and pvdE was targeted and deleted in P. fluorescens. The deletion of pyoverdine could lead to a biofilm-to-motivity transition of P. fluorescens. The deletion of pyoverdine affect the spoilage potential of P. fluorescens in the refrigerated sterilized fish juice. Pyoverdine is involved in the regulation of transcription levels of htpX, phoA, flip, flgA and rpoS of P. fluorescens.